2013
DOI: 10.1007/s00894-013-1832-x
|View full text |Cite
|
Sign up to set email alerts
|

A large gap opening of graphene induced by the adsorption of CO on the Al-doped site

Abstract: We investigated CO adsorption on the pristine, Stone-Wales (SW) defected, Al- and Si- doped graphenes by using density functional calculations in terms of geometric, energetic and electronic properties. It was found that CO molecule is weakly adsorbed on the pristine and SW defected graphenes and their electronic properties were slightly changed. The Al- and Si- doped graphenes show high reactivity toward CO, so calculated adoption energies are about -11.40 and -13.75 kcal mol(-1) in the most favorable states.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…As shown by the calculated DOS and the energy gaps (E g ) between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) in Table 1, the pure sheet is found to be a semi-metallic material with the E g of 0.25 eV, in agreement with Peyghan et al [29] work. Weak interaction is evident in the DOS structure, which shows little change after the adsorption.…”
Section: Resultssupporting
confidence: 89%
“…As shown by the calculated DOS and the energy gaps (E g ) between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) in Table 1, the pure sheet is found to be a semi-metallic material with the E g of 0.25 eV, in agreement with Peyghan et al [29] work. Weak interaction is evident in the DOS structure, which shows little change after the adsorption.…”
Section: Resultssupporting
confidence: 89%
“…In addition, other DFT studies have shown the ability of Al and Fedoped graphene for adsorption of several classes of pollutants such as p-nitrophenol [21], dioxane [22], acetyl halides [23], formaldehyde [24], transition metals [25], and small gas molecules (such as HCN, CO, SO 2 , N 2 O, etc) [26][27][28][29], among others; the doping of other nanostructures as C 3 N nanosheets has proven also to increase the adsorption strength of analites [30]. Note that the dopants in graphene are capable to decrease the structural work associated with the activation energies [31,32]; in addition, Al and Fe atoms improve the binding of the substrate with lone-pair containing adsorbates because they behave as Lewis acids, and these dopants show a low-cost and benign behavior with the environment [28].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, one-dimensional layer of carbon with sp 2 hybridization, is in the center of attention for gas sensing due to its high electronic mobility, and unique thermal, mechanical, electrical, optical, and chemical properties [21][22][23][24][25][26]. It has been found that the pristine graphene is not suitable for HCOH detection, and previous studies made an effort to overcome this problem by functionalization of graphene with polymers, metals, or other modifiers to generate dangling bonds on the surface [27,28].…”
Section: Introductionmentioning
confidence: 99%